2015
DOI: 10.1080/09571736.2015.1053281
|View full text |Cite
|
Sign up to set email alerts
|

Getting used to content and language integrated learning: what can classroom interaction reveal?

Abstract: Bilingual programmes in which an L2 is used as the medium of instruction are becoming popular in different parts of the world, and content and language integrated learning (CLIL) is one variant of such programmes. Recent research on CLIL has gradually shifted from product-oriented (i.e. evaluating the effectiveness of CLIL in terms of language and content learning outcomes) to more process-oriented by exploring classroom interaction in detail to gain insight into effective pedagogy and teacher education. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 36 publications
2
21
0
1
Order By: Relevance
“…Contrary to the stereotypes of many critical voices who claim that physical activity levels decrease in Physical Education with CLIL (Coral et al, 2017;Martinez and Garcia, 2017), we did find evidence in both the interviews and accelerometry results that the quality of physical activity is not necessarily diminished. In addition, despite some teachers' concerns about their explanations being longer when applying CLIL (Lo and Macaro, 2015;Salvador-García and Chiva-Bartoll, 2017), the percentage of time that students were engaged in MVPA was also maintained.…”
Section: Discussion Of Qualitative and Quantitative Findingsmentioning
confidence: 97%
“…Contrary to the stereotypes of many critical voices who claim that physical activity levels decrease in Physical Education with CLIL (Coral et al, 2017;Martinez and Garcia, 2017), we did find evidence in both the interviews and accelerometry results that the quality of physical activity is not necessarily diminished. In addition, despite some teachers' concerns about their explanations being longer when applying CLIL (Lo and Macaro, 2015;Salvador-García and Chiva-Bartoll, 2017), the percentage of time that students were engaged in MVPA was also maintained.…”
Section: Discussion Of Qualitative and Quantitative Findingsmentioning
confidence: 97%
“…That means many students who have not had experience in class or at school where English is used in science learning. Lo & Macaro (2015) concluded that there were differences in language skills among students who had recently adopted bilingual learning with schools that had long adopted the learning. This factor of experience can affect language skills.…”
Section: Indicatormentioning
confidence: 99%
“…One possible reason for the apparent success of CLIL has to do with the kinds of communicative contexts it makes available to learners and the effect of these contexts on both their opportunities to use the language and their motivation to engage with it. Classroom observations of CLIL classes have shown the learners tend to participate more actively in subject-learning classes than language-input classes and have benefited from the programme in terms of eagerness to volunteer and classroom verbal output (Huang, 2011;Lo & Macaro, 2015). Nikula (2010: 120) notes that in the CLIL lessons students have "more room for active engagement in classroom discourse than non-CLIL settings".…”
Section: Content and Language Integrated Learningmentioning
confidence: 99%
“…Other studies, however, have reported reduced active student participation in CLIL classrooms. In a study by Lim Falk (2008), CLIL students were found to use less relevant subject-based language in speech and writing than did the control students, and a study by Lo and Macaro (2015) in Hong Kong found that, at least at the beginning stages, teacherstudent interaction in CLIL lessons was more monologic and teacher dominated, and that students often had difficulties expressing their meanings in L2. Some researchers (e.g.…”
Section: Content and Language Integrated Learningmentioning
confidence: 99%